Getting Rid of Performance Ratings: Genius or Folly? A Debate. Issue 2 (4th July 2016) - Adler, Seymour; Campion, Michael; Colquitt, Alan; Grubb, Amy; Murphy, Kevin; Ollander-Krane, Rob; Pulakos, Elaine D.
Abstract : Despite years of research and practice, dissatisfaction with performance appraisal is at an all-time high. Organizations are contemplating changes to their performance management systems, the most controversial of which is whether to eliminate performance ratings. The pros and cons of retaining performance ratings were the subject of a lively, standing-room-only debate at the 2015 Society for Industrial and Organizational Psychology conference in Philadelphia (Adler, 2015 ). Given the high interest in this topic, this article recaps the points made by the panelists who participated in the debate. The arguments for eliminating ratings include these: (a) the disappointing interventions, (b) the disagreement when multiple raters evaluate the same performance, (c) the failure to develop adequate criteria for evaluating ratings, (d) the weak relationship between the performance of ratees and the ratings they receive, (e) the conflicting purposes of performance ratings in organizations, (f) the inconsistent effects of performance feedback on subsequent performance, and (g) the weak relationship between performance rating research and practice in organizations. The arguments for retaining ratings include (a) the recognition that changing the rating process is likely to have minimal effect on the performance management process as a whole, (b) performance is always evaluated in some manner, (c) "too hard" is no excuse for industrial–organizational (I-O) psychology, (d) ratings and differentiated evaluations have many merits for improving organizations, (e) artificial tradeoffs are driving organizations to inappropriately abandon ratings, (f) the alternatives to ratings may be worse, and (g) the better questions are these: How could performance ratings be improved, and are we conducting the entire performance management process properly? The article closes with questions organizational members have found useful for driving effective performance management reform.